Social Beliefs and Ergonomics on Traditional Seat of Wooden Furniture Review of Related Literature - Paul Benedict Inkum; Na Yu; Wu Zhihui (Borong Newinera Publisher, 2020)
The main purpose of this review paper was to highlight Social Beliefs and Ergonomics on Traditional Seat of Wooden Furniture Review of Related Literature. More specifically, the review of limited literature on traditional seat of wooden furniture in view of ergonomics which characterized the basic structure, safety, functions and aesthetics properties. The paper then provides possible solutions to redesign traditional seats that promote healthier sitting behaviours centered on appropriate configuration of its components. The paper also explores the cross-cultural considerations associated with traditional seat furniture design.